Are people willing to share living space? Household preferences in Finland - Enni Ruokamo; Eliisa Kylkilahti; Michael Lettenmeier; Anne Toppinen (Buildings & Cities)
This paper explores citizens’ interest in space sharing in private housing. It is based on a large-scale random sample citizen survey (N = 1448) conducted in Finland focusing on multiple aspects of low-carbon housing. Both quantitative preference-related results and qualitatively analysed open question responses show that the concept of shared space use is relatively low in popularity. However, there are differences depending on the space to be shared. Approximately half of the respondents are willing to use shared space for exercise, children playing and repairing activities, whereas a small fraction would use it for cooking, working and studying, or guest accommodation. Respondents’ backgrounds only slightly impact the willingness to share spaces. However, people in urban areas are more willing to share spaces. Larger floor area per inhabitant is negatively associated with the willingness to share spaces. This implies that sufficiency in housing is linked with space-sharing interests. This paper concludes that space-sharing is relatively unattractive under present conditions. Improving functionality and social trust by attractive design, clearer user rules and spreading good examples could be approaches to enhance the situation. Practice relevance Space-sharing as an operationalisation of housing sufficiency could be an attractive avenue for increasing the utilisation rate and efficiency of space use among households. Based on the results from a survey of Finnish citizens, space-sharing received somewhat mixed responses, although 75% of respondents indicated at least some willingness for sharing activities. Respondents with high climate-change awareness and those living in urban areas are associated positively with an interest in space-sharing. Future development needs to increase the attractiveness of sharing spaces include paying attention to the design of shared spaces, formulating clear user rules, creating functional booking and fee systems, and building awareness towards responsible user practices.